Synthesis, Spectral, Thermal and Biological Studies of Some Metal Complexes Derived from Heterocyclic Mono Azo Dye Ligand 2'[(2'-Hydroxy-4-methyl phenyl)azo]imidazole - Al-Adilee, Khalid J.; Atyha, Saad A. (Asian Journal of Chemistry, 2017)
A new hetrocyclic mono azo dye ligand 2'[2'-(1-hydroxy-4-methyl phenyl)azo]imidazole (HMePAI) was prepared by reaction between diazonium chloride salt solution of 2'-amino-4-methyl phenol with imidazole in alkaline ethanolic solution. Nine metal complexes with Cr(III), Mn(II), Fe(III), Co(III), Ni(II), Cu(II), Zn(II), Cd(II) and Hg(II) ions were prepared and characterized by analytical and spectral techniques like elemental analysis (CHN), metal contents, molar conductance, magnetic moments, 1H NMR, Mass spectra, infrared, electronic spectral, XRD spectra, SEM and thermal studies (TGA & DSC). The results indicated that the ligand (HMePAI) behaves as a tridentate in case of 1:2 [metal:ligand] complexes. Investigation of the stereochemistry of metal complexes have octahedral geometry. Biological activity of ligand (HMePAI) and its metal complexes against two types of bacteria, Staphylococcus aureus (Gram-positive) and Escherichia coli (Gram-negative) by agar plate different technique. The biological activity was also conducted by cells viability and cytotoxicity assay on ligand and Ni(II) complex by using the lines of cancerous liver cells of the type HEPG2 and compared with line of the ordinary cells.